The European Commission's enhanced Rule of Law mechanism - Molly O'Neal (Stiftung Wissenschaft und Politik (SWP), 2019)
The new European Commission has signaled its commitment to advance the work of its predecessor in asserting European Union (EU) authority to prevent - and, if necessary, respond to - breaches in the rule of law by member states. A new toolbox of measures to accomplish this aim would build upon the Rule of Law Framework, adopted in 2014, and rulings by the Court of Justice of the European Union (CJEU) requiring compliance by member country courts and judicial systems with EU legal principles of judicial independence and separation of powers. The first two principal aims of the reinforced toolbox of measures are to foster, through public outreach, a rule of law culture across the EU, and to expand the scope of monitoring and reporting to all member countries while deepening the Commission's institutional expertise to achieve a timely and detailed understanding of developments. The third aim is to reinforce the leverage of the EU to respond in cases where there is serious deviation from rule of law norms. This latter aspect of the reinforced "toolbox" includes adopting a strategic approach to bringing anti-infringement cases to the CJEU and the introduction of rule of law conditionality to EU funding in member countries.
Keywords: 320